Causes of death and mortality trends of all individuals reported with HIV/AIDS in Israel, 1985–2010. (17th June 2017) - Mor, Zohar; Sheffer, Rivka; Chemtob, Daniel
Abstract: Background: Highly active antiretroviral therapy (HAART) has changed life-expectancy and mortality trends among people living with HIV/AIDS (PLWHA) since 1996. This retrospective cohort study aimed to assess the mortality epidemiology of PLWHA in Israel and analyze the causes of death. Methods: This cohort study included all adult Israeli-citizens PLWHA between 1985 and 2010 and crossed matched with the Civil Registry to identify those who died. Death certificates were classified into AIDS or non-AIDS deaths related-causes. Standardized mortality-ratio (SMR) represented mortality excess. Results: Of all 5140 PLWHA who were followed-up for 36 955 person-years, 1066 (20.7%) died. The ratio of AIDS-related deaths to non-AIDS related deaths reduced from 1.2:1 before 1996 to 0.6:1 after 1997, and case-fatality rates reduced from 12.0 to 0.9%, respectively ( P < 0.001). SMR were 3.0 (95% CI: 2.3–3.5) for males and 3.9 (95% CI: 3.3–4.5) for females. Fatality cases were more likely older Israeli-born males, co-infected with tuberculosis, reported before 1996 and acquired HIV by drug-injection or infected-blood products. Deaths of AIDS-related causes were common among Israeli-born gay men, while non-AIDS deaths were common among those reported after 1997 and drug users. Conclusions: Death rates declined since HAART introduction. Yet, SMR remained high, and PLWHA infected by drug-use or blood-products have not enjoyed relative longevity.